2019
DOI: 10.1007/s00248-019-01444-1
|View full text |Cite
|
Sign up to set email alerts
|

Food Web Uncertainties Influence Predictions of Climate Change Effects on Soil Carbon Sequestration in Heathlands

Abstract: Laender, F. (2020). Food web uncertainties influence predictions of climate change effects on soil carbon sequestration in heathlands. Microbial ecology, 79(3), 686-693.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…Despite this, they have only recently been included in general models of ecosystem services (de Vries et al, 2014), probably because of their immense diversity. However, uncertainties in consumers' preferences in soil food webs can strongly influence model predictions (Reyns et al, 2019). A main obstacle in food web models is the traditional, simplistic, but erroneous assumption that soil protists act only as bacterivores -however, protists occupy all trophic levels, also including, autotrophs, mixotrophs, saprotrophs, eukaryvores, omnivores, as well as parasites of animals and plants and their hyperparasites (Geisen et al, 2016;Bonkowski et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite this, they have only recently been included in general models of ecosystem services (de Vries et al, 2014), probably because of their immense diversity. However, uncertainties in consumers' preferences in soil food webs can strongly influence model predictions (Reyns et al, 2019). A main obstacle in food web models is the traditional, simplistic, but erroneous assumption that soil protists act only as bacterivores -however, protists occupy all trophic levels, also including, autotrophs, mixotrophs, saprotrophs, eukaryvores, omnivores, as well as parasites of animals and plants and their hyperparasites (Geisen et al, 2016;Bonkowski et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Despite of this, they have only recently been included in general models on ecosystem services (de Vries et al, 2014), probably because of their immense diversity. However, uncertainties in consumers' preferences in soil food webs can strongly influence model predictions (Reyns et al, 2019). A main obstacle in food web models is the traditional simplistic, but erroneous assumption that soil protists act only as bacterivores -instead protists occupy all trophic levels, and include, next to bacterivores, autotrophs, mixotrophs, saprotrophs, eukaryvores, omnivores, as well as parasites of animals and plants and their hyperparasites (Geisen et al, 2016;Bonkowski et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Shifts in soil community composition (e.g. bacteria: fungi ratio) and activity due to environmental stressors can therefore have significant consequences for carbon cycling 46,47 . Therefore, the fact that previous work on the site demonstrated that belowground biology in the restored heath was not yet comparable to that of the native heathland 31 may have implications for the soil carbon in our field study.…”
Section: Discussionmentioning
confidence: 99%